Association between vitamin D levels and preserved ratio impaired spirometry: an investigation of mediating roles of systemic inflammation and metabolic indicators - Lin, Tong; Huang, Shanshan; Zhou, Fen; Shen, Xingkai; Mao, Haiyan (Frontiers in Nutrition, 2025)
BackgroundPreserved ratio impaired spirometry (PRISm) represents an abnormal lung function state distinct from traditional chronic obstructive pulmonary disease, characterized by unique clinical and epidemiological features. PRISm has been associated with various health issues, including an increased risk of metabolic disorders and cardiovascular diseases. Vitamin D, known for its anti-inflammatory, immunomodulatory, and antioxidant properties, may play a role in reducing the risk of PRISm. This study aims to investigate the relationship between vitamin D levels and PRISm, including the mediating effects of systemic inflammation markers and metabolic indicators in a population of U.S. adults.MethodsThis cross-sectional study analyzed data from 17,333 participants from the U.S. National Health and Nutrition Examination Survey, including 1,577 individuals with PRISm and 15,756 without. Baseline characteristics were assessed, and multivariate logistic regression models were employed to examine the relationship between vitamin D and PRISm. Mediation analysis was conducted to explore potential mediating roles of systemic immune-inflammation index (SII), triglyceride-glucose (TyG) index, and bilirubin. Nonlinear relationships were assessed using restricted cubic spline (RCS) models.ResultsThe PRISm group had lower median vitamin D levels and distinct inflammatory and metabolic profiles compared to the non-PRISm group. Multivariate analysis confirmed an inverse association between vitamin D levels and PRISm (adjusted OR: 0.989, 95% CI: 0.984–0.994, p < 0.001). RCS analysis showed a nonlinear protective effect of vitamin D, with risk stabilizing at levels above 50 nmol/mL. Mediation analysis highlighted bilirubin as a positive mediator (ACME = −4.11 × 10−5, p < 0.001), while TyG demonstrated a suppressive mediation effect (ACME = 2.68 × 10−5, p < 0.001). SII did not show significant mediation.ConclusionElevated vitamin D levels are linked to a lower risk of PRISm, with bilirubin potentially acting as a mediator in this protective relationship. This underscores the clinical significance of maintaining sufficient vitamin D levels to promote lung health and mitigate the prevalence of PRISm among U.S. adults. Further research is warranted to investigate personalized vitamin D supplementation strategies as a potential preventive approach.